Consumption foodstuffs originating from exotic animals - Dovč, Alenka (Array, 2019)
Exotic animals such as Iberian pigs, zebras, kangaroos, ostriches, camels, crocodiles, pythons, and some others can be, lately more often, found on the menus of Western European restaurants. In third world countries such food can be found in street sales. Despite the stringent regulations in force in the EU, there is also an illegal market for listed foods which, in this case, represent a significant risk to the health of consumers, and trade in those foods threatens the welfare of animals, traded and domestic because different diseases could be transmitted from imported animals or foodstuffs originating from them. The meat of exotic animals is distinguished by its specific characteristics compared to that of domestic animals, and those are highlighted in this article, and mention is made of the consumption of numerous insects, common in some countries. Consuming certain foods, from the standpoint of the average European consumer, is even of questionable deliciousness (balut) or ethics (blood of venom snake).